Persistent organic pollutants in female humpback whales Megaptera novaeangliae from the Gulf of Maine. (1st January 2023) - Baugh, Keri A.; Robbins, Jooke; Schultz, Irvin R.; Ylitalo, Gina M.
Abstract: Contaminant studies in cetaceans can provide information about pollutant levels and patterns in a given region. Due to the confounding effects of reproductive status and maternal offloading in females, these studies typically focus on males. However, an improved understanding of contaminant burdens in female cetaceans is needed to better assess potential impacts to populations. The objectives of this study were to characterize concentrations of persistent organic pollutants (POPs) in blubber of female humpback whales across age classes and to also better characterize maternal offloading of these pollutants to their offspring. A total of 36 blubber biopsy samples of female humpback whales ( Megaptera novaeangliae ) from the Gulf of Maine were analyzed to examine contaminant loads across females of different ages. Sampled individuals were individually-identified from longitudinal studies and assigned to age class (i.e., adult, subadult, juvenile, calf). Analysis was performed using gas chromatography/mass spectrometry (GC/MS) of POPs including polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethanes (DDTs), chlordanes (CHLDs), polybrominated diphenyl ethers (PBDEs), hexachlorocyclohexanes (HCHs). The most abundant POPs were PCB congeners, with summed values ranging from 280 to 12, 000 ng/g, lipid weight, which is above recent estimates of the threshold for adverse health effects. We found significant differences in mean values between adults and juveniles and between adults and subadults, with the exception of the less persistent HCHs for the latter. We also found significant differences in mean levels of ∑HCHs between the juveniles and subadults. Changes over age are consistent with maternal offloading and potentially important for evaluating population health and viability. Graphical abstract: Image 1 Highlights: The most abundant POPs in humpback whales were ∑PCBs then ∑DDTs and then ∑CHLDs. Levels of POPs in humpback whales were highest in juveniles and lowest in adults. The highest ∑PCBs concentration in the juveniles was 12, 000 ng/g lipid weight.